2014
DOI: 10.1021/nl500149h
|View full text |Cite
|
Sign up to set email alerts
|

Dielectrophoresis-Enhanced Plasmonic Sensing with Gold Nanohole Arrays

Abstract: We experimentally demonstrate dielectrophoretic concentration of biological analytes on the surface of a gold nanohole array, which concurrently acts as a nanoplasmonic sensor and gradient force generator. The combination of nanohole-enhanced dielectrophoresis, electroosmosis, and extraordinary optical transmission through the periodic gold nanohole array enables real-time label-free detection of analyte molecules in a 5 µL droplet using concentrations as low as 1 pM within a few minutes, which is more than 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
157
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(158 citation statements)
references
References 50 publications
0
157
0
1
Order By: Relevance
“…In addition, a large-area golden nanohole arrays integrated with conductive glass (indium tin oxide: ITO) were also used to demonstrate the dielectrophoresis (DEP)-enhanced SPR sensing. Governed molecules diffuse to the sensor and are significantly accelerated by using applied AC electric field forces on the BSA molecules, as shown in Figure 4 [48]. It is found that the fabricated nanostructure enables label-free and real-time detection of target molecules in the concentrations as low as 1 pM in very short time.…”
Section: Pef From Nanohole Array Substratementioning
confidence: 97%
See 1 more Smart Citation
“…In addition, a large-area golden nanohole arrays integrated with conductive glass (indium tin oxide: ITO) were also used to demonstrate the dielectrophoresis (DEP)-enhanced SPR sensing. Governed molecules diffuse to the sensor and are significantly accelerated by using applied AC electric field forces on the BSA molecules, as shown in Figure 4 [48]. It is found that the fabricated nanostructure enables label-free and real-time detection of target molecules in the concentrations as low as 1 pM in very short time.…”
Section: Pef From Nanohole Array Substratementioning
confidence: 97%
“…Governed molecules diffuse to the sensor and are significantly accelerated by using applied AC electric field forces on the BSA molecules, as shown in Figure 4. [48] It is found that the a result, the investigation of enhanced fluorescence effect of many typical nonperodical nanostructure, such as silver island film (SiF), fractal-like substrate, on fluorescence have been widely performed.…”
Section: Pef From Nonperiodical Metallic Plasmonic Nanostructurementioning
confidence: 99%
“…The limit of detection far exceeds previously reported label-free optical sensing-based results and can be further improved by using molecule-concentrating techniques and post-measurement signal processing. [54][55][56] The work presented in this manuscript can directly lead to development of convenient label-free optical sensors for large-scale on-chip screening of pancreatic islets required for islet transplantation therapy. The future direction will also be aimed at improving the specificity of hormone detection using these substrates in media such as blood.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…However, their sensing capability is generally limited by the relatively low sensitivity, broad spectral linewidth and weak resonance intensity [10][11]. The reported refractive index (RI) sensitivities (detection limits) for these nanoplasmonic sensors are one to two orders of magnitude lower (larger) than those of typical prism-based sensing systems [12][13]. Another widely used nanoplasmonic sensing technique is SPP interferometry, which uses the phase-sensitive interference to control the linewidth of the interference pattern, which may improve the sensing resolution [14][15][16].…”
Section: Introductionmentioning
confidence: 99%